Accepting Other Religion and Live Harmoniously: A Study on Malaysian Youth - Ahmad Zaharuddin Sani Ahmad Sabri; Roziya Abu; Shamshuritawati Sharif; Rozira Abu (Online Journal of Research in Islamic Studies, 2021)
In a multicultural, multi-ethnic and multi-religious nation like Malaysia, inter-ethnic harmony is seen as both an enriching society and a government obstacle. A diverse community with disparities in culture, language and religion is often viewed as difficult to control because of the many different needs, beliefs and aspirations of different communities within a multicultural society. The inter-ethnic peace and stability of Malaysia’s society helping the country to prosper economically is often praised. While there is no violent confrontation between ethnic groups, as ethnic differences exist along political, socio-economic and geographical lines, a sense of national unity proves difficult to achieve. This study was conducted to analyse the involvement of Malaysian youth in the inter-ethnic unity conversation. A survey was distributed among 735 youth in Northern peninsular region of Malaysia, using indicators of social harmony index. In order to assess whether there were any variations between the three major ethnic groups on the religion acceptance. The findings showed that there were some gaps in the hunt for accepting each other believe. The discrepancies between the Malays and the Chinese were most pronounced among these activities, with the Chinese showing comparatively lower levels of acceptance compared to the Malays, and lower levels of nation unity compared to both the Malays and the Indians.